Photoresponsive metallopolymer nanoparticles for cancer theranostics. (August 2021) - He, Maomao; Chen, Fangman; Shao, Dan; Weis, Philipp; Wei, Zhiyong; Sun, Wen
Abstract: Over the past decades, transition metal complexes have been successfully used in anticancer phototherapies. They have shown promising properties in many different areas including photo-induced ligand exchange or release, rich excited state behavior, and versatile biochemical properties. When encorporated into polymeric frameworks and become part of nanostructures, photoresponsive metallopolymer nanoparticles (MPNs) show enhanced water solubility, extended blood circulation and increased tumor-specific accumulation, which greatly improves the tumor therapeutic effects compared to low-molecule-weight metal complexes. In this review, we aim to present the recent development of photoresponsive MPNs as therapeutic nanomedicines. This review will summarize four major areas separately, namely platinum-containing polymers, zinc-containing polymers, iridium-containing polymers and ruthenium-containing polymers. Representative MPNs of each type are discussed in terms of their design strategies, fabrication methods, and working mechanisms. Current challenges and future perspectives in this field are also highlighted.